Muscular Strength and Incident Hypertension in Normotensive and Prehypertensive Men - Maslow, Andréa L. (2010)
The protective effects of cardiorespiratory fitness (CRF) on hypertension (HTN) are well known; however, the association between muscular strength and incidence of HTN has yet to be examined. PURPOSE: This study evaluated the strength-HTN association with and without accounting for CRF. METHODS: Participants were 4147 men (20–82 years) in the Aerobics Center Longitudinal Study for whom an age-specific composite muscular strength score was computed from measures of a 1-repetition maximal leg and a 1-repetition maximal bench press. CRF was quantified by maximal treadmill exercise test time in minutes. Cox proportional hazards regression analysis was used to estimate hazard ratios (HRs) and 95% confidence intervals of incident HTN events according to exposure categories. RESULTS: During a mean follow-up of 19 years, there were 503 incident HTN cases. Multivariable-adjusted (excluding CRF) HRs of hypertension in normotensive men comparing middle and high strength thirds to the lowest third were not significant at 1.17 and 0.84, respectively. Multivariable-adjusted (excluding CRF) HRs of hypertension in baseline prehypertensive men comparing middle and high strength thirds to the lowest third were significant at 0.73 and 0.72 (p=.01 each), respectively. The association between muscular strength and incidence of HTN in baseline prehypertensive men was no longer significant after control for CRF (p=.26). CONCLUSIONS: The study indicated that middle and high levels of muscular strength were associated with a reduced risk of HTN in prehypertensive men only. However, this relationship was no longer significant after controlling for CRF.